First, rewrite the equation as:
#3.8x^2 - color(red)(4.7x) + color(blue)(2.1) = 4.7x - color(red)(4.7x) - 2.1 + color(blue)(2.1)#
#3.8x^2 - 4.7x + 2.1 = 0 - 0#
#3.8x^2 - 4.7x + 2.1 = 0#
Now, we can use the quadratic equation to solve this problem:
The quadratic formula states:
For #color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0#, the values of #x# which are the solutions to the equation are given by:
#x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))#
Substituting:
#color(red)(3.8)# for #color(red)(a)#
#color(blue)(-4.7)# for #color(blue)(b)#
#color(green)(2.1)# for #color(green)(c)# gives:
#x = (-color(blue)((-4.7)) +- sqrt(color(blue)((-4.7))^2 - (4 * color(red)(3.8) * color(green)(2.1))))/(2 * color(red)(3.8))#
#x = (4.7 +- sqrt(22.09 - 31.92))/7.6#
#x = (4.7 +- sqrt(-9.83))/7.6#